PENERAPAN ALGORITMA K.MEANS UNTUK PENENTUAN PENCOCOKAN PEWARNAAN CLUSTERING SECARA OTOMATIS PADA PRODUK FASHION - Instianti Elyana (LPPM Universitas Bina Sarana Informatika, 2015)
Many the needs of the people especially to find products fashion being suitable and appropriate using a web to the needs of user but many web market products fashion make levels color is needed to looking for a match with the skin and the proportion of the body .The need for the measurement of levels color for it was very needed to search products fashion required with classifications uses the method algorithm k-means to get accuracy color being suitable and to clustering staining approaching search products fashion for example by color selection to model suit that in conformity with the wish .It is expected that with this research will help the people to determine match use of color in the fashion desired .The research results show that this method can reduce ketidakakuratan 25 % , so that color later is produced and same in image color will look homogeneous and this study shows the percentage Failure or error rate by more or less under 20 %.